PERILAKU MEMILIH PEMILIH PEMULA MASYARAKAT KENDAL PADA PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 - KHAIRUL AZMI; Puji Astuti; FITRIYAH . (Journal of Politic and Government Studies, 2016)
Voting behavior in the presidential election is a set of activities to determine thedecision in choosing the president and vice president. In the 2014, the number ofyoungvoters of presidential election were very significant to win the electioninIndonesia, about 20-30% of the total number of voters areyoungvoters. Based onsurvey of Lembaga Survei Nasionalyoungvoters behavior included in thecategory of rational approach. This study to analyze theyoungvotersbehaviorinKendalon Election of President and Vice President using sociological approach,psychological approach, and the approach of rational choice.This research is using quantitative approach with survey method. The samplingtechnique in this studyusing Multi Stage Random Sampling with 100 respondents.This study using a questionnaire to collecting data.The results showed thatyoungvoters is using their voting rights rationally.Beginner voters ignore sociological factors, they ignored age and professionalbackground of presidential candidates, but the education and gender of beginnervoters influence their political choices.Maleyoungvoters tend to choose a matePrabowo-Hatta, while femaleyoungvoters tend to choose Jokowi-Jusuf Kalla.Basedon psychological approaches, candidates figur had larger role than bearerparty. Based on rational approaches,youngvoters believe that president theyhave chosen can alleviate poverty, enforce laws, and improve welfare.For the next researcher who willconduct research on the same topic, researchershope this study can be perfected, by using a triangulation method. Keywords: voting behavior,youngvoters